2017
DOI: 10.3389/fcimb.2017.00086
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis Serotype 2 Biofilms Inhibit the Formation of Neutrophil Extracellular Traps

Abstract: Invasive infections caused by Streptococcus suis serotype 2 (SS2) has emerged as a clinical problem in recent years. Neutrophil extracellular traps (NETs) are an important mechanism for the trapping and killing of pathogens that are resistant to phagocytosis. Biofilm formation can protect bacteria from being killed by phagocytes. Until now, there have only been a few studies that focused on the interactions between bacterial biofilms and NETs. SS2 in both a biofilm state and a planktonic cell state were incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…https://www.ors.org/wp-content/uploads/2018/11/Biofilm-Question-3.pdf addresses biofilm susceptibility to host phagocytosis. While neutrophils and macrophages (10–20 μm) have the ability to access the surface and enter the channels of a mature biofilm (100 μm), they are not able to access biofilm encased microorganisms . When a fragment of biofilm is small enough, phagocytes can engulf it, but they are not able to destroy the bacteria .…”
Section: Resultsmentioning
confidence: 99%
“…https://www.ors.org/wp-content/uploads/2018/11/Biofilm-Question-3.pdf addresses biofilm susceptibility to host phagocytosis. While neutrophils and macrophages (10–20 μm) have the ability to access the surface and enter the channels of a mature biofilm (100 μm), they are not able to access biofilm encased microorganisms . When a fragment of biofilm is small enough, phagocytes can engulf it, but they are not able to destroy the bacteria .…”
Section: Resultsmentioning
confidence: 99%
“…Interesting results were obtained recently by Ma et al [94] who demonstrated experimentally that S. suis type 2 can form biofilms in vivo in some murine tissues, such as the liver, spleen and kidney. The bacteria in the biofilms were not phagocytized.…”
Section: Importance Of Biofilm Formationmentioning
confidence: 99%
“…Biofilm formation increased up to 6-fold in the presence of neutrophils and the biofilm extracellular matrix can inhibit release of the neutrophil extracellular traps (NETs) and increase the survival of bacteria in the blood. Nevertheless, the protection is not complete and according to the authors NETs appear to be an important mechanism to eliminate S. suis biofilms [94].…”
Section: Importance Of Biofilm Formationmentioning
confidence: 99%
“…Periodontal disease caused by polymicrobial synergy among periodontal bacteria in subgingival biofilms may be successful in their colonization of the region through their NET degradation capacities (367). It has been reported in a few studies that biofilm formation can inhibit NETs and this can be attributed to the extracellular matrix structure, as detached planktonic bacteria can induce NETs (398). NET formation is an effective mechanism employed by neutrophils to respond to infection, therefore, lack of NET formation has disease promoting implications.…”
Section: Discussionmentioning
confidence: 99%